Studi Kawasan Kerentanan Longsor pada Ruas Jalan Cikajang Pamengpeuk KM BDG 88+200 S/D 147+790 - Gariballah Sharief; Adi Susetyaningsih (Institut Teknologi Garut, 2023)
Development progress and land clearing along the Cikajang-Pameungpeuk KM BDG Road Section. 99+800 to 147+790 increases, this can influence the occurrence of landslides. This research aims to determine the level of landslide vulnerability along the Cikajang-Pameungpeuk KM BDG 99+800 S/D 147+790 Road Section. The method used is overlay and weighting using 4 landslide susceptibility parameters. From the results of combining the data obtained, in Cikajang District it shows that it is prone to landslides, there are three landslide points, in Banjarwangi District it shows that it is less prone to landslides, there are no landslide points, in Cihurip District it shows that it is less prone to landslides there is one point of landslides, in Cisompet District it shows that it is very There are seven points prone to landslides and in Pameungpeuk District it shows that it is less prone and there are no landslide points.